Mapping the lipidomic secretome of the early equine embryo - Lawson, Edwina F.; Pickford, Russell; Aitken, Robert John; Gibb, Zamira; Grupen, Christopher G.; Swegen, Aleona (Frontiers in Veterinary Science, 2024)
The lipidomic secretions of embryos provide a unique opportunity to examine the cellular processes of the early conceptus. In this study we profiled lipids released by the early equine conceptus, using high-resolution mass spectrometry to detect individual lipid species. This study examined the lipidomic profile in embryo-conditioned media from in vivo-produced, 8–9 day-old equine embryos (n = 3) cultured in vitro for 36 h, analyzed over 3 timepoints. A total of 1,077 lipid IDs were recorded across all samples, containing predominantly glycerolipids. Seventy-nine of these were significantly altered in embryo conditioned-media versus media only control (p < 0.05, fold-change >2 or < 0.5). Fifty-five lipids were found to be released into the embryo-conditioned media, of which 54.5% were triacylglycerols and 23.6% were ceramides. The sterol lipid, cholesterol, was also identified and secreted in significant amounts as embryos developed. Further, 24 lipids were found to be depleted from the media during culture, of which 70.8% were diacylglycerols, 16.7% were triacylglycerols and 12.5% were ceramides. As lipid-free media contained consistently detectable lipid peaks, a further profile analysis of the various components of non-embryo-conditioned media consistently showed the presence of 137 lipids. Lipid peaks in non-embryo-conditioned media increased in response to incubation under mineral oil, and contained ceramides, diacylglycerols and triacylglycerols. These results emphasize the importance of a defined embryo culture medium and a need to identify the lipid requirements of the embryo precisely. This study sheds light on early embryo lipid metabolism and the transfer of lipids during in vitro culture.